Physiological Responses and Metabonomics Analysis of Male and Female Sargassum thunbergii Macroalgae Exposed to Ultraviolet-B Stress - Sun, Yan; Liu, Qian; Shang, Shuai; Chen, Jun; Lu, Peiyao; Zang, Yu; Tang, Xuexi (Frontiers in Plant Science, 2022)
Ultraviolet-B (UV-B) radiation is a major environmental stress that suppresses or activates defense responses in organisms. UV-B radiation affecting growth and development in intertidal species have been researched for a long time, but a series of unknown knowledge remain in the male and female macroalgae comparison. To compare the different responses of male and female Sargassum thunbergii macroalgae under UV-B radiation, PSII photochemical efficiency determination, metabolomic analysis, and main carbon-based metabolites (including soluble sugar, total amino acid, and lipid) content measuring have been performed in our experiments. Results showed that males have significantly superiority performance in the chlorophyll fluorescence parameters of Fv/Fm, Y(II), and Y(NO) either low or high UV-B radiation treatments. Metabolomics analysis revealed that carbon and nitrogen metabolism pathways in male and female S. thunbergii were significant components responding to enhanced UV-B radiation. Based on measuring, female S. thunbergii lipid content expressed higher than males without any stimulation. Additionally, under low UV-B radiation stimulation, females total amino acid content shown significantly higher than control group and their lipid content also significantly higher than males. Under high UV-B radiation, males soluble sugar, total amino acid, and lipid content significantly varied from females, which meant that enhancing UV-B stress might altered mainly carbon-based metabolites flowing directions. The present study elucidated the potential role of enhanced UV-B radiation in regulating macroalgae physiological responses, metabolites changing, and reflecting differences between male and female S. thunbergii, contributing to understanding of brown-macroalgae diecious adopting mechanisms in defending intertidal UV-B stresses.